2008
DOI: 10.1038/emboj.2008.106
|View full text |Cite
|
Sign up to set email alerts
|

Branch migration enzyme as a Brownian ratchet

Abstract: In recent years, it has been shown that helicases are able to perform functions beyond their traditional role in unwinding of double-stranded nucleic acids; yet the mechanistic aspects of these different activities are not clear. Our kinetic studies of Holliday junction branch migration catalysed by a ring-shaped helicase, T7 gp4, show that heterology of as little as a single base stalls catalysed branch migration. Using single-molecule analysis, one can locate the stall position to within a few base pairs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
0
31
1
Order By: Relevance
“…Our results also show unambiguously that the torsion-absorbing, non-B-DNA structure in the alternating GC sequence cannot be a cruciform, because such a structure would yield a higher FRET efficiency than the B-DNA state (38), contrary to our present observations.…”
Section: Discussioncontrasting
confidence: 57%
“…Our results also show unambiguously that the torsion-absorbing, non-B-DNA structure in the alternating GC sequence cannot be a cruciform, because such a structure would yield a higher FRET efficiency than the B-DNA state (38), contrary to our present observations.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been shown that even a single heterologous base pair is able to block the spontaneous branch migration of a four-way junction (Biswas et al, 1998), whereas single-stranded breaks do not hinder spontaneous branch migration (Palets et al, 2010). Branch migration catalyzed by T7 gp4 was stalled by a single heterologous base pair (Rasnik et al, 2008). We investigated how these DNA structural features affected the branch migration reversal of WRN.…”
Section: Resultsmentioning
confidence: 99%
“…T7 gp4 can move along single stranded (ss) (11) or double stranded (ds) (12) DNA and separate DNA strands using the energy of dTTP hydrolysis. The protein can also synthesize short (4–5 -mer) RNA primers using ATP and CTP at priming sites on the lagging DNA strand.…”
Section: Introductionmentioning
confidence: 99%